A theory of crime resistance and susceptibility - Agnew, Robert (Criminology, 2016)
The “causes of crime” research has up to this point focused on those events and conditions that push or pressure individuals into crime (strains), that pull or attract individuals to crime (social learning for crime), and that restrain individuals from responding to pressures and attractions with crime (controls). Work in several areas, however, has suggested that the response to the pressures for and attractions to crime is not simply a function of controls. It is also a function of the individual's resistance or susceptibility to the events and conditions described by strain and social learning theories. Those high in resistance are less likely to experience these criminogenic events and conditions as pressures for or attractions to crime, whereas those high in susceptibility are more likely. Resistance and susceptibility are a function of factors that influence the perception and interpretation of criminogenic events and conditions, the emotional reaction to them, and the behavioral inclinations prompted by them. These factors include negativity, pleasure and sensation seeking, conventional efficacy and perceived social support, and general sensitivity to the environment. With certain notable exceptions, these factors have been neglected in mainstream crime research, but they have the potential to improve the explanation and prediction of crime substantially.